The Ideal Model for Resolving Land Disputes between Rice Farmers and Industrial Companies in Karawang Regency - Ismail Rumadan; Pri Pambudi Teguh; Umar Husin; Ummu Salamah; Masidin; Hamrin; Ika Mayasari (Law Doctoral Community Service Journal, 2023)
Conflicts over agricultural land in Karawang Regency often occur between communities cultivating rice fields and companies. This conflict was triggered because Karawang Regency is one of the areas in West Java that is an investment destination, so the need for land is getting more significant for developing investment, especially in the industrial sector. This need then has implications for the transfer of land functions and the occupation of land owned by rice cultivators in Karawang Regency. This condition then creates an unavoidable conflict between sharecropper communities and companies that invest in the Karawang district. One ideal option for resolving conflicts between the community and the company is mediation. The choice places the parties in a balanced way to secure the interests of each, which can provide guarantees of legal certainty for the parties.